The Role of Religious Leaders in Social Development and Interreligious Harmony: A Historical-Sociological Study of Islamic Leaders in the 21st Century - Khusnul Khotimah (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: The focus of this research discusses the role of religious leaders in social development and religious harmony in the 21st century. Objective: To analyze and understand the influence of religious leaders on social and religious dynamics in Banyumas Regency in the 21st century. Method: The approach used in this research is an interdisciplinary approach with qualitative methods. The research was conducted in Banyumas Regency. The subjects were families, colleagues, students, and community leaders who had interacted with religious figures from Banyumas who passed away in the 21st century. Data collection techniques included documentation, participant observation, and in-depth interviews. The data were analyzed using qualitative descriptive analysis. Result: Religious leaders in Banyumas play a very important role in various aspects of community life, including religion, education, politics, and economics. Conclusion: The presence and leadership of religious figures significantly influence the development of social and religious harmony in Banyumas. Contribution: This research provides a deeper understanding of how religious leaders contribute to social-religious development, offering valuable insights for future community empowerment and interfaith harmony strategies.